Postcards from another mad afternoon at home : collected notes & drawings on windows, doors, pipes (Atelier HOKO, 2019)
HOKO Studio is a research studio founded in 2002 by Alvin Ho and Clara Ko. This book is a collection of more than 300 postcard-sized notes as part of the research and exploration of the Science of the secondary series. In this series, windows, doors and plumbing are chosen as the starting point for the study of the home, and it is an attempt to explore the various bodily experiences of individuals and build a closer and more intimate relationship between people and buildings by using everyday actions and habituations such as exercising in the comfort of one's own home. The many responses obtained from this activity, in the form of notes and drawings, were compiled into a postcard-sized publication that expands in parallel in time and space through collective participation. They focus on people, face the unknown, look at reality with fresh and sharp eyes, and maintain a high level of curiosity about all phenomena.
English Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions